2017
DOI: 10.1159/000480473
|View full text |Cite
|
Sign up to set email alerts
|

CNTN-1 Enhances Chemoresistance in Human Lung Adenocarcinoma Through Induction of Epithelial-Mesenchymal Transition by Targeting the PI3K/Akt Pathway

Abstract: Background/Aims: Chemoresistance has been a major obstacle to the effective treatment of lung cancer. Previously, we found that contactin-1 (CNTN-1) is related to cisplatin resistance in lung adenocarcinoma. Here, we aimed to investigate the underlying mechanism behind the role of CNTN-1 in cisplatin resistance in lung adenocarcinoma. Methods: EMT-associated phenotypes, including alterations in cellular morphology and marker (E-cadherin, N-cadherin and Vimentin) expression, were compared between A549 cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 54 publications
4
32
0
Order By: Relevance
“…The PI3K/Akt signaling pathway is proved to be a promising target in cancer therapy for its contributions to cell proliferation, EMT and chemoresistance in various tumors. CNTN-1 promotes phosphorylation of Akt protein, thus increasing its activity, and an interrelation between CNTN-1 and the Akt signal has been reported [28,29]. In the present study, by silencing CNTN-1 in PCa, PI3K/ Akt signaling, EMT and Dox resistance were distinctly inhibited, and the effect of CNTN-1 knockdown was partially abolished by using the PI3K activator IGF-1 at the same time.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The PI3K/Akt signaling pathway is proved to be a promising target in cancer therapy for its contributions to cell proliferation, EMT and chemoresistance in various tumors. CNTN-1 promotes phosphorylation of Akt protein, thus increasing its activity, and an interrelation between CNTN-1 and the Akt signal has been reported [28,29]. In the present study, by silencing CNTN-1 in PCa, PI3K/ Akt signaling, EMT and Dox resistance were distinctly inhibited, and the effect of CNTN-1 knockdown was partially abolished by using the PI3K activator IGF-1 at the same time.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, CNTN-1 was demonstrated to promote the development of various cancers including lung, squamous, hepatocellular, gastric and prostate cancer [30,[37][38][39][40][41]. Aberrant CNTN-1 was discovered to aggravate tumor invasion, metastasis, EMT and chemoresistance in lung cancer [29]. In PCa, CNTN-1 exacerbated in vitro cell invasion and in vivo tumor growth and lung metastasis in PCa [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows the ability for metastasis and invasion of cancer cells after EMT is remarkably enhanced, and these mesenchymal-like cells are strongly resistant to targeted drugs or radio- or chemotherapy. 63 – 65 Tumor cells after EMT express high levels of stem surface markers, indicating that these cells have become stem-like cells. 66 – 68 One interesting study revealed that breast CSCs originate from the fusion of M2-TAMs and breast cancer cells; these hybrid cells overexpress mesenchymal-associated genes and stemness markers.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“…Several potential chemoresistance mechanisms involving EMT have been suggested (34,35). It is well-known that EMT occurs during tumor migration and invasion, and facilitates tumor progression (36).…”
Section: Discussionmentioning
confidence: 99%